Effectiveness of a Health Belief Model–Based “Smart Social Media” Module in Reducing Social Media Addiction Among Indonesian Adolescents: A Quasi-Experimental Study - Ana Sofyana; Arif Widodo (STIKep PPNI Jawa Barat, 2026)
Background: Adolescent social media addiction has become a growing public health concern in Indonesia, particularly in semi-urban areas, and is linked to negative mental health and academic outcomes. Previous intervention studies often lacked rigorous control designs and contextual relevance, limiting their generalizability. Objective: This study evaluated the effectiveness of a structured Health Belief Model (HBM)–based “Smart Social Media” module in reducing social media addiction and improving knowledge among Indonesian adolescents. Methods: A quasi-experimental non-equivalent control group design was conducted among 70 senior high school students in Sukoharjo, Indonesia. Participants were assigned to an intervention group (n = 35) or control group (n = 35). The intervention consisted of a single 45-minute session including an educational presentation, interactive HBM-based discussion with a Kahoot quiz, and completion of a social media diary worksheet. Social media addiction and knowledge were measured using a validated 20-item questionnaire (Cronbach’s α = 0.927). Data were analyzed using Wilcoxon signed-rank and Mann–Whitney U tests (α < 0.05). Results: The intervention group showed a significant increase in knowledge (median change +16.0, p < 0.001) and a significant reduction in social media addiction scores (median change −4.0, p < 0.001), with large effect sizes. The control group showed minimal changes. Between-group post-test differences were statistically significant for both outcomes. Conclusion: The HBM-based “Smart Social Media” module was effective in reducing social media addiction and improving knowledge among adolescents. Larger multi-site and longitudinal studies are recommended to assess sustained behavioral effects